Heritability of late blight resistance in tomato conferred by Solanum pimpinellifolium accession PI 224710. Issue 4 (2nd June 2015) - Ohlson, Erik W.; Foolad, Majid R.; Altpeter, F.
Abstract Late blight (LB), caused by the oomycete Phytophthora infestans, is one of the most destructive diseases of tomato and potato worldwide. Identifying and characterizing new sources of resistance is essential given the emergence of new aggressive and fungicide‐resistant P. infestans isolates. Recently, we reported identification of several new sources of LB resistance within the tomato wild species, Solanum pimpinellifolium. In this study, we examined heritability (h2) of LB resistance conferred by the S. pimpinellifolium accession PI 224710 using a parent–offspring regression (correlation) analysis. F2 and F3 progeny populations, derived from crosses between PI 224710 and a LB‐susceptible tomato breeding line, were evaluated for response to LB infection. To obtain a better estimate of h2, the F3 progeny were evaluated for LB resistance in two separate replicated experiments. The h2 estimates were similar in the two experiments and averaged 0.87, suggesting that this resistance was highly heritable. Two different methods estimated involvement of one resistance locus. Breeding and mapping efforts are underway to further assess the viability of this newly reported LB resistance.